Could Painful Experience in the Neonatal Period Trigger Persistent Anxiety-Like Behavior? - Nathalia Leilane Berto Machado; Elisabete de Cássia do Carmo; Luciana Sayuri Sanada; Valeria Paula Sassoli Fazan (Journal of Psychological Disorders, 2019)
We used a behavioral test to investigate long-term consequences of neonatal noxious stimulus in the anxiety-like behavior and describe differences between males and females. Male and female Wistar rats were submitted to either tactile (control groups) or noxious stimulus (pain groups) since birth, for 15 days and were followed up to 6 months of life. Experiments were performed on days 15, 30, 90 and 180 after birth. Rats of different groups, ages and genders were exposed only once to the elevated plus-maze (EPM), an apparatus largely used to detect anxiety-related behaviors in rats. For the open arms of the EPM, control animals showed an increase in the number of entries from 15 to 30 days of age followed by a decrease of this number at older ages. The comparison between treatments (control and pain) showed, for males, a reduced number of entries in the open arms in the pain group at 15 and 30 days and the opposite situation at 180 days. No differences were found between pain and control groups in females. Our results are in agreement with the literature that shows sex-dependent changes following chronic stress; stress being anxiolytic in males and anxiogenic in females. We point to the fact that acute painful stimulus in the neonatal period caused persistent changes in anxiety-like behavior in the adult life, independently of previously described intrinsic gender differences on memory, task performance, attention bias or other behaviors.
Keywords: Neonatal pain